Articular syndrome in an HIV-infected patient - O. S. Malyshenko; T. A. Raskina; Yu. V. Averkieva; T. V. Protasova; A. M. Dubaeva (Современная ревматология)
Nowadays, HIV infection is one of the leading health problems. Its clinical signs are extremely diverse and are associated with many diseases, including rheumatic diseases. This paper describes the course of articular syndrome in a patient with HIV infection. In the patient given, asymmetric arthritis of the left wrist, first metacarpophalangeal, and knee joints with no damage to the skin and mucous membranes or enthesitis, a negative HLA-B27 test, and the whole clinical picture, as well as no convincing evidence of rheumatic diseases might suggest the presence of arthritis associated with HIV infection. The diagnosis of HIV infection was verified using enzyme immunoassay. Today, knowledge continues to accumulate about the features of the course of joint damages and another rheumatic disease in the presence of HIV infection. The possibility of its existence to mask a rheumatic disease, as well as the mutual aggravation of any of the diseases and AIDS, should be taken into account in the practice of physicians of all specialties, especially in the inpatient setting where difficult and diagnostically difficult cases concentrate.